Electrical performance of lithium ion based polymer electrolyte with polyethylene glycol and polyvinyl alcohol network. Issue 15 (12th October 2016) - Pandey, Mayank; Joshi, Girish M.; Ghosh, Narendra Nath
ABSTRACT: A solid polymer electrolyte based on lithium hydroxide (LiOH) added with polyethylene glycol and polyvinyl alcohol polymers was synthesized by solution casting. The structural variation with respect to loading wt% of LiOH reveals the semicrystalline property of polymer electrolyte. The differential scanning calorimetry data shows the onset of crystalline to amorphous transition, which occurs nearly to the melting peak, for higher salt content. The structural properties and cross-linking between polymer and salt were demonstrated by polarized optical microscopy. The polymer electrolytes were subjected to AC impedance analysis spectra for obtaining the ionic conductivity at different temperature. The charge carriers relax much faster for higher lithium salt concentration based polymer electrolyte and produces higher conductivity. The highest room temperature conductivity 2.63 × 10 −5 S/cm is obtained for 8 wt% loading of lithium salt based polymer electrolyte, confirming their use in preparation of ion conducting devices. GRAPHICAL ABSTRACT: